Loupe-Assisted Vasovasostomy Using a Prolene Stent: A Simpler Vasectomy Reversal Technique - Jong Chul Jeon; Taekmin Kwon; Sejun Park; Sungchan Park; Sang Hyeon Cheon; Kyung Hyun Moon (The World Journal of Men's Health, 2017)
Purpose: Microsurgical vasovasostomy is associated with high patency and pregnancy rates, but is difficult and requires significant effort and time to learn. Therefore, we assessed a simplified loupe-assisted vasovasostomy method using a Prolene stent. Materials and Methods: The medical records of 82 patients who underwent loupe-assisted vasovasostomy with a Prolene stent by a single surgeon between January 2004 and December 2015 were reviewed. The association between the vasal obstructive interval (VOI) and the success rate was evaluated. Results: The average age at the time of vasovasostomy was 39.8 years (range, 29∼57 years). The mean VOI was 6.6 years (range, 1∼19 years). The mean operation time was 87.0 minutes (range, 55.0∼140.0 minutes). The overall patency and natural pregnancy rates were 90.2% and 45.1%, respectively. The success rate decreased as time after vasectomy increased (odds ratio, 0.869; 95% confidence interval, 0.760∼0.993; p=0.039). The cases were divided into 2 groups according to the mean VOI: group A (＞7 years) and group B (≤7 years), with 31 cases (37.8%) and 51 cases (62.2%), respectively. The patency and pregnancy rates of group A were 80.6% and 51.6%, respectively, while those of group B were 96.1% and 41.2%, respectively. Conclusions: Loupe-assisted vasovasostomy using a Prolene stent is a safe and effective method.